2013
DOI: 10.1063/1.4811391
|View full text |Cite
|
Sign up to set email alerts
|

Error-field penetration in reversed magnetic shear configurations

Abstract: Error-field penetration in reversed magnetic shear (RMS) configurations is numerically investigated by using a two-dimensional resistive magnetohydrodynamic model in slab geometry. To explore different dynamic processes in locked modes, three equilibrium states are adopted. Stable, marginal, and unstable current profiles for double tearing modes are designed by varying the current intensity between two resonant surfaces separated by a certain distance. Further, the dynamic characteristics of locked modes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…21 Moreover, in the core regime, Cromb e et al investigated the plasma poloidal rotation velocity across internal transport barriers (ITBs) on JET, revealing a very clear link between the steepest region of the ion temperature gradient and localized spin-up of poloidal velocity. 22 Although the present magnetohydrodynamic (MHD) theories 11,17,23 and modellings [24][25][26][27][28][29] of plasma response to static RMPs have already discovered some significant roles of plasma flows with respect to the mode penetration, they are still far from establishing a self-consistent complete picture concerning the NPV. This drives further physical and numerical improvements of the relevant underlying understanding.…”
Section: Introductionmentioning
confidence: 99%
“…21 Moreover, in the core regime, Cromb e et al investigated the plasma poloidal rotation velocity across internal transport barriers (ITBs) on JET, revealing a very clear link between the steepest region of the ion temperature gradient and localized spin-up of poloidal velocity. 22 Although the present magnetohydrodynamic (MHD) theories 11,17,23 and modellings [24][25][26][27][28][29] of plasma response to static RMPs have already discovered some significant roles of plasma flows with respect to the mode penetration, they are still far from establishing a self-consistent complete picture concerning the NPV. This drives further physical and numerical improvements of the relevant underlying understanding.…”
Section: Introductionmentioning
confidence: 99%
“…-The nonlinear evolution of the DTMs induced by the error field has been shown in ref. [17]. It has been found that the DTMs can be locked by the error field when the rotation is very small [17].…”
mentioning
confidence: 99%
“…In these works, the onset of DTMs has been generally considered as a result of the localized initial magnetic perturbation at the rational surfaces. In actual experiments, however, the magnetic perturbation may also appear on the plasma boundary, such as error field, resonant magnetic perturbation (RMP) [12][13][14][15][16][17]. Therefore, studies about the effect of RMP on the DTM are important to well understand the triggering mechanism of the DTM.…”
mentioning
confidence: 99%
See 2 more Smart Citations